2013
DOI: 10.1128/ec.00319-12
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Defective Endoplasmic Reticulum-Associated Degradation Pathway on the Stress Response, Virulence, and Antifungal Drug Susceptibility of the Mold Pathogen Aspergillus fumigatus

Abstract: Proteins that are destined for release outside the eukaryotic cell, insertion into the plasma membrane, or delivery to intracellular organelles are processed and folded in the endoplasmic reticulum (ER). An imbalance between the level of nascent proteins entering the ER and the organelle's ability to manage that load results in the accumulation of unfolded proteins. Terminally unfolded proteins are disposed of by ER-associated degradation (ERAD), a pathway that transports the aberrant proteins across the ER me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 41 publications
2
22
0
Order By: Relevance
“…Moreover, the Δ derA /Δ hacA mutant was avirulent, which contrasted the wt virulence of Δ derA and the partial virulence of Δ hacA 50 . Similar findings were observed by deleting the hrdA gene, encoding a ubiquitin ligase that is part of the same ERAD complex 51 . Together, these findings established that ERAD cooperates with the UPR to support functions of the secretory pathway that are necessary for virulence.…”
Section: The Upr: a Regulatory Hub For Virulence Traitssupporting
confidence: 62%
“…Moreover, the Δ derA /Δ hacA mutant was avirulent, which contrasted the wt virulence of Δ derA and the partial virulence of Δ hacA 50 . Similar findings were observed by deleting the hrdA gene, encoding a ubiquitin ligase that is part of the same ERAD complex 51 . Together, these findings established that ERAD cooperates with the UPR to support functions of the secretory pathway that are necessary for virulence.…”
Section: The Upr: a Regulatory Hub For Virulence Traitssupporting
confidence: 62%
“…Yet another possibility is proteasomal degradation independent of DerA. In A. fumigatus it has been demonstrated that deletion of the ERAD gene hrdA in addition to the deletion of derA highly increased the susceptibility to ER stressing agents such as tunicamycin (Krishnan et al 2013), indicating that DerA and HrdA have synergistic functions. Further studies are required to explore the proteasomal pathway either by making double knockout mutants of the ERAD system or by applying proteasome inhibitors like MG132 (Kautto et al 2013) and the fluorescent mtGlaA::GFP protein could be used as a reporter to monitor protein accumulations under these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…; Krishnan et al. ). Deletion of the der1 homolog derA in a heterologous protein overexpression strain of Aspergillus niger resulted in a sixfold increase in the intracellular accumulation of the protein accompanied by the induction of UPR target genes, but had no effect on growth and conidiation (Carvalho et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disposal of any proteins that ultimately fail to achieve an appropriate conformation is accomplished by ERAD, a pathway that is regulated in part by the UPR (Travers et al, 2000). The deletion of the ERAD genes derA or hrdA had no effect on the virulence of A. fumigatus (Krishnan et al, 2013; Richie et al, 2011). However, the combined loss of derA and hacA caused a more severe reduction in hyphal growth, antifungal drug resistance and protease secretion than the loss of either gene alone.…”
Section: Human Fungal Pathogensmentioning
confidence: 97%